Chimeric antigen receptor T cell therapy for multiple myeloma - Kana Hasegawa; Naoki Hosen (Inflammation and Regeneration, 2019)
Abstract Chimeric antigen receptor (CAR) T cell therapy is a new cancer immunotherapy targeting cancer-specific cell surface antigen. CD19-CAR T cells have been already shown to be very effective to B cell leukemia/lymphoma. Now, many researchers are developing CAR T cells for multiple myeloma. CAR T cells targeting B cell maturation antigen (BCMA) showed promising efficacy in early phase clinical trials. We have recently reported that CAR T cells targeting the activated integrin β7 can selectively eradicate MM cells including CD19+ clonotypic B cells and are preparing a clinical trial.